Preparation of nanoparticles by laser ablation on copper target in distilled water - Aye H.L. (2014)
Preparation of nanoparticles by pulsed Nd:YAG (1064 nm) laser ablation on copper target submerged in distilled water has been studied. Effects of pulse power and liquid height were investigated. Colloidal nanoparticles were characterized by UV-Vis spectroscopy, Raman dynamic light scattering and transmission electron microscopy. The concentration of nanoparticles was increased with the pulse power at a particular liquid height or volume. The size of nanoparticles related complicatedly to both parameters. The optimum conditions were the pulse power of 80 W and the liquid height of 3-4 mm. The obtained mean particle size was 20-37 nm, having the maximum UV-Vis absorption wavelength at 617-630 nm. The colloids contained mainly copper oxide nanoparticles. © (2010) Trans Tech Publications.